Retirement planning among young professionals in private sector / Mohammad Firdaus Ghazali - Ghazali, Mohammad Firdaus (Faculty of Business and Management, 2015)
This project paper is conducted as to fulfill the partial requirement by Faculty of Business Management, MARA University of Technology (UiTM). The purpose of this study is to determine the association between financial literacy, job satisfaction and savings behaviour towards retirement planning among young professionals in private sector. Data used for this study are primary and secondary data such as from journal articles, textbook and also via internet. Therefore, a structural questionnaire is distributed and administered to collect data from the respondents in order to answer the research questions of this study. A total of 100 respondents of young professionals in private sector who aged between 20 until 34 years old participated in this study. Based on frequency analysis, reliability test, mean analysis and Pearson correlations in this study, a clear findings and results are obtained. The findings show that financial literacy, job satisfaction and savings behaviour has a positive association towards retirement planning. As such, the conclusion of this study is the outcome from the findings and survey analysis. A researcher also provides some recommendations and suggestions on how to improve and encourage young professionals in private sector to have a better retirement planning.